Preparation and Characterization of (Hyacinth plant / Chitosan) Composite as a Heavy Metal Removal - Taha et al. (مجلة بغداد للعلوم, 2019)
In this study, the preparation and characterization of hyacinth plant /chitosan composite, as a heavy metal removal, were done. Water hyacinth plant (Eichhorniacrasspes) was collected from Tigris river in Baghdad. The root and shoot parts of plant were ground to powder. Composite materials were prepared at different ratios of plant part (from 2.9% to 30.3%, wt /wt) which corresponds to (30-500mg) of hyacinth plant (root and shoot) and chitosan. The results showed that all examined ratios of plant parts have an excellent absorption to copper (Cu (II)). Moreover, it was observed that 2.9% corresponds (30mg) of plant root revealed highest removal (82.7%) of Pb (II), while 20.23% of shoot removed 61% of Cd (II) within 24 hr. On the other hand, SEM images displayed a regular shape and high porosity of prepared samples, while FTIR spectra of composite materials showed the characteristic of raw materials bands, which give strong evidence of composite formation.